Antithrombotic strategy in cancer patients comorbid with acute coronary syndrome and atrial fibrillation - Wang, Tianbo; Liu, Xiaohan; Zhu, Yuxin; Zhang, Yue; Zhang, Zhen; Huang, Gang; Xu, Junbo (Frontiers in Cardiovascular Medicine, 2023)
It has been shown that patients with cancer have a longer expected life duration, benefiting from advanced medical therapy. Meanwhile, the risk of suffering from cardiovascular disease (CVD) has been increasing with ageing. A growing number of studies have elucidated the association between cancer and CVD. Cancer, atrial fibrillation (AF) and coronary artery disease share some common factors and interact with each other, such as obesity, aging, diabetes, and inflammation, but the potential specific mechanism is still unclear. In addition, cancer-specific and therapy-related factors may increase the risk of embolism and bleeding in patients with cancer than in general population. However, current available embolic and bleeding risk scores applied in patients with CVD may not be applicable for risk assessment in cancer patients, which would be difficult for clinicians to select an appropriate antithrombotic regimen and ensure the balance between bleeding and embolism. Moreover, different types of cancer have distinct risks, which may increase the complexity of antithrombotic therapy. In this review, we review the literature related to cancer, AF, and acute coronary syndrome, focusing on the epidemiological status, physiological mechanism, embolism and bleeding risks, and strategies of antithrombotic therapy.